Jesaja 40:1-2 - Suiwer evangelie! - Silva, A. A. da (Hervormde teologiese studies, 1990)
Isaiah 40:1-2 - Pure gospel! This article endeavours to analize Isaiah 40:1-2 in such a way that ministers who are experiencing difficulties in preaching the Old Testament might find in it some guidelines on a workable way in which sections of the Old Testament could be analized with the purpose of making a sermon about it. The method employed consists of four steps, namely a general orientation, a synchronic analysis, a diachronic analysis and a reception-critical analysis. The results show that Isaiah 40:1-2 is pure gospel! It speaks in no way less than the New Testament about God’s redemption of the sinner through his grace alone!